Effects of precocene and Azadirachtin in Rhodnius Prolixus: some data on development and reproduction - Garcia, Eloi S. (1987)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Bioquímica e Biologia Molecular. Rio de Janeiro, RJ, Brasil.